2016
DOI: 10.1038/ncomms10566
|View full text |Cite
|
Sign up to set email alerts
|

Spectral phase measurement of a Fano resonance using tunable attosecond pulses

Abstract: Electron dynamics induced by resonant absorption of light is of fundamental importance in nature and has been the subject of countless studies in many scientific areas. Above the ionization threshold of atomic or molecular systems, the presence of discrete states leads to autoionization, which is an interference between two quantum paths: direct ionization and excitation of the discrete state coupled to the continuum. Traditionally studied with synchrotron radiation, the probability for autoionization exhibits… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
114
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(123 citation statements)
references
References 38 publications
1
114
2
1
Order By: Relevance
“…These narrow autoionization resonances, observed for the first time in HHS from N 2 , are not completely resolved at this harmonic spacing, but are still clearly evident and contribute to the zig-zag behavior in both the spectrum and group delay between 20 and 30 eV. The zig-zag feature might also be contaminated by the Fano resonance in the argon detection gas around 26 eV [50], however, the strong angular dependence of our group delay measurements shows that the detection gas is not the main source of this zig-zag shape. Based on the comparison with theory, the largest feature in the experimental group delay at …”
mentioning
confidence: 87%
“…These narrow autoionization resonances, observed for the first time in HHS from N 2 , are not completely resolved at this harmonic spacing, but are still clearly evident and contribute to the zig-zag behavior in both the spectrum and group delay between 20 and 30 eV. The zig-zag feature might also be contaminated by the Fano resonance in the argon detection gas around 26 eV [50], however, the strong angular dependence of our group delay measurements shows that the detection gas is not the main source of this zig-zag shape. Based on the comparison with theory, the largest feature in the experimental group delay at …”
mentioning
confidence: 87%
“…In the language of perturbation theory similar effects are expressed by the reversed time-order of photon interactions. While it has been understood for a long time that the simple additive relation is not valid close to atomic resonances [14,30,31], it has now been experimentally shown that the simple relation breaks down also in angular-resolved measurements from the isotropic ground state of helium [16]. The latter effect is especially strong for photoelectron emission close to the nodes of the photoelectron angular distributions where the probability of electron emission is low.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal characterization of attosecond pulses, which requires determination of the spectral phase of the XUV field, can be performed by laser-assisted photoionization [4,5]. More recently, this type of experiments have been used for spectral phase determination of photoelectrons from autoionizing states [6,7] and for the measurement of relative time delays in laser-assisted photoionization from different initial states in solids [8] and atoms [9][10][11]. Relative time delays have also been measured between different atomic species [12][13][14], between single and double ionization [15], between different angles of photoemission [16] and between the ion ground state and shake-up states [17].…”
Section: Introductionmentioning
confidence: 99%
“…The respective next sidebands will however be unaffected and can serve as reference to extract the phase associated with the resonance. This technique was applied to study the phase in two-colour two-photon ionization of helium [22] and more recently to measure the phase evolution of a Fano resonance in argon [23]. Fano resonances are a very general phenomenon in physics, characterized by an asymmetric line shape that originates from the interference between a resonant process and a background [24]; in atomic systems, between direct photoionization to the continuum and excitation to a quasi-bound state above the ionization potential, which will rapidly decay (within femtoseconds) to the …”
Section: Further Developmentsmentioning
confidence: 99%